1994
DOI: 10.1182/blood.v84.12.4053.bloodjournal84124053
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential hot spots in the carboxy-terminal part of the Epstein-Barr virus (EBV) BNLF-1 gene in both malignant and benign EBV-associated diseases: high frequency of a 30-bp deletion in Malaysian and Danish peripheral T-cell lymphomas

Abstract: In this study, we have sequenced the C-terminal part of the Epstein- Barr virus (EBV)-BNLF-1 gene encoding for the latent membrane protein-1 from tissues of EBV-positive Danish Hodgkin's disease (HD) and of Danish and Malaysian peripheral T-cell lymphomas (PTLs) and from tonsils of Danish infectious mononucleosis (IM). Our study showed that some of the 7 single-base mutations and the 30-bp deletion previously detected between codons of amino acid 322 and 366 in the BNLF-1 gene of the nasopharyngeal carcinoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 33 publications
7
59
0
Order By: Relevance
“…Since the first published studies regarding the prevalence of EBV strains that EBV type 1 was described as the most predominant worldwide [Sample et al, 1990]. Literature shows that, despite the possible existence of coinfections, EBV type 1 is the predominant variant worldwide, especially in Caucasian and Asian populations while EBV type 2 is more frequently found in Africa [Apolloni and Sculley, 1994;Sandvej et al, 1994;Kim et al, 2002;Garc ıa-Cos ıo et al, 2008;Tiwawech et al, 2008;Chang et al, 2009;Bobek et al, 2010]. Nevertheless, there are very few studies in Africa.…”
Section: Ebv Strainsmentioning
confidence: 99%
“…Since the first published studies regarding the prevalence of EBV strains that EBV type 1 was described as the most predominant worldwide [Sample et al, 1990]. Literature shows that, despite the possible existence of coinfections, EBV type 1 is the predominant variant worldwide, especially in Caucasian and Asian populations while EBV type 2 is more frequently found in Africa [Apolloni and Sculley, 1994;Sandvej et al, 1994;Kim et al, 2002;Garc ıa-Cos ıo et al, 2008;Tiwawech et al, 2008;Chang et al, 2009;Bobek et al, 2010]. Nevertheless, there are very few studies in Africa.…”
Section: Ebv Strainsmentioning
confidence: 99%
“…A recent in vitro study has shown that del-LMP1 is associated with 30-70% prolongation of the half-life of the mutant protein. 25 Since LMP1 expression within human B lymphocytes induces DNA synthesis, abrogates apoptosis and plays an important role in the initiation and ⁄ or maintenance of the immortalized state, it is possible that the effects of LMP1 may be accentuated through loss of a genome segment required for its rapid turnover. Alternatively, cells with del-LMP1 may express an altered protein product with decreased immunogenecity for EBV-specific cytotoxic T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, peculiar deletions within the BamH1-N left-ward open reading frame-1 gene encoding the LMP-1 of EBV (so called 30-base pair (bp) deletion or 69 bp deletion) were evidenced in EBV genome-positive tumor cells with HD, NPC or peripheral T-cell lymphoma (17)(18)(19). Interestingly, LMP-1 may stimulate intercellular and intracellular signal transduction pathways, including nuclear factor-kappa B, a transcriptional factor controlling the expression of genes, involved in cell activation and growth control (20,21).…”
Section: Biology Of Ebv and Immune Eventsmentioning
confidence: 99%
“…Interestingly, LMP-1 may stimulate intercellular and intracellular signal transduction pathways, including nuclear factor-kappa B, a transcriptional factor controlling the expression of genes, involved in cell activation and growth control (20,21). However, the fact that the 30-bp deletion and 6 of 7 single-base mutations was found as frequently in tonsils of acute IM (19). More recently, it was reported 30-bp deletion of LMP-1 had no prognostic significance of LPD which occurred in recipients with organ transplantation and was only reflective of the incidence of EBV strain in the regional population (22).…”
Section: Biology Of Ebv and Immune Eventsmentioning
confidence: 99%
See 1 more Smart Citation